Proposed Customer Experience to Increase Cashless Payment at Gas Stations in Bandung City (The Indonesian Journal of Business Administration, 2021)
Telkom has been assigned by Pertamina to provide digital payment service at gas station and create positive experience as such customers could change their behavior from cash payment to cashless payment, and in turn taking part for the success of Government's program in the Gerakan Nasional Non Tunai (GNNT) or Non-Cash National Movement. However, the number of cashless payments is still smaller in number compare to cash payments. This research was conducted with the objectives, first, to analyze factors those could significantly influence customer experience in using digital payment; and second, to develop customer experience strategy as an effort to increase cashless payment behavior at the gas stations. To help finding the root causes of this problem, the author used mix-methodology of qualitative and quantitative research. First, external analysis of macro environment, industry environment, competitor, and consumers of gas station was conducted consecutively using four methods, i.e., PEST Analysis, Porter Five Forces, Competitor Analysis, and Consumer Analysis. Second, internal analysis toward Telkom company was conducted using three methods, i.e., Marketing Mix, STP, and VRIO Analysis. As the result, this study generates six root causes or problem relates to convenience, brand trust, substitute product, limited features, promotion, and target market, which indicates the need to improve customer experience at Pertamina gas station. Therefore, the authors proposed nine customer experience strategy based on significant factors those influence customer experience in using digital payment; and as an effort to increase cashless payments at Pertamina gas station. Keywords: Digitalization gas stations, Telkom, Customer Experience, Digital Payment